Studies on avian salmonellosis in West Bengal - CHAKRABORTY, DHRUBA; CHAKRABORTY, GOPAL CHANDRA; CHATTERJEE, AMARESH (The Indian Journal of Animal Sciences, 2012)
Strains (25) of Salmonella gallinarum were isolated from 69 samples collected from diseased birds, each having characteristic signs and gross lesions belonging to different age groups of broiler, layer and cockrail distributed in 69 farms, situated at different districts of West Bengal. The isolates were characterized on the basis of morphological, cultural and biochemical reactions. Epidemiology and pathogenicity of the avian salmonellosis was discussed. Antimicrobial sensitivity test against 10 antimicrobial agents revealed multiple drug resistant strains of Salmonella. Cephotaxime, chloramphenicol and cirprofloxacin were most effective whereas furazolidine and amoxycillin were least effective.Â